MOTION GRAPHIC SEBAGAI MEDIA SOSIALISASI TENTANG PUBLIC RELATION UNTUK KARYAWAN OWNTALK.CO.ID - Disca Eki Wulansari; Arta Uly Siahaan (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2021)
The development of technology in various aspects is very influential in the field of information and communication. This development can be proven by the existence of motion graphics. One company that implements motion graphics is Owntalk.co.id. Owntalk.co.id is an online news media site that was established on August 19, 2019. As a new company that is 2 years old, currently, Owntalk.co.id needs a public relations division that functions to improve the company's image and build relationships through its employees. This study aims to socialize public relations through the creation of motion graphics that are unique and easy to understand by employees of Owntalk.co.id. The benefit of public relations socialization using motion graphics is the establishment of an understanding of public relations therefore the employees can implement public relations activities according to their roles and functions. This research uses the Luther Sutopo design method, with 6 stages of concept, design, collecting, assembly, testing, and distribution materials. In this study, the results were in the form of a motion graphics video with a duration of 2 minutes 33 seconds with a percentage of 96.8%, which means that this motion graphics video is useful for Owntalk.co.id in disseminating public relations materials to its employees.